2009
DOI: 10.1242/jeb.016329
|View full text |Cite
|
Sign up to set email alerts
|

Limiting factors to encapsulation: the combined effects of dissolved protein and oxygen availability on embryonic growth and survival of species with contrasting feeding strategies

Abstract: SUMMARYEncapsulation is a common strategy among marine invertebrate species. It has been shown that oxygen and food availability independently constrain embryo development during intracapsular development. However, it is unclear how embryos of species with different feeding strategies perceive these two constraints when operating jointly. In the present study, we examined the relative importance of dissolved albumen, as a food source, oxygen condition and their interaction on embryonic growth and the survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 38 publications
1
37
0
Order By: Relevance
“…One of the main challenges for encapsulated embryos, such as L. obtusata, is probably O 2 supply, as embryos are often crowded within egg masses and the jelly matrix around the eggs limits O 2 diffusion (Brante et al, 2009). Furthermore, intertidal habitats are subject to large P O2 fluctuations (Truchot and Duhamel-Jouve, 1980;Agnew and Taylor, 1986) and embryos in egg masses have no possibility of avoiding hypoxic areas once the egg mass has been deposited in one location and can therefore be exposed to hypoxic conditions for longer periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main challenges for encapsulated embryos, such as L. obtusata, is probably O 2 supply, as embryos are often crowded within egg masses and the jelly matrix around the eggs limits O 2 diffusion (Brante et al, 2009). Furthermore, intertidal habitats are subject to large P O2 fluctuations (Truchot and Duhamel-Jouve, 1980;Agnew and Taylor, 1986) and embryos in egg masses have no possibility of avoiding hypoxic areas once the egg mass has been deposited in one location and can therefore be exposed to hypoxic conditions for longer periods.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst many gastropod egg capsules are considered to be freely permeable to water (e.g. Galtsoff et al, 1937;Carriker, 1955;Pechenik, 1983), the jelly matrix enclosing the embryos has been found to constrain oxygen diffusion into the egg mass (Brante et al, 2009). Furthermore, embryos are often crowded within egg masses and are frequently exposed to large fluctuations in O 2 partial pressure (P O2 ) in the intertidal zone (Raffaelli and Hawkins, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, no cannibalism during development was reported in the buccinids B. cyaneum (Miloslavich and Dufresne 1994) and B. isaotakki (Ilano et al 2004), and only very rarely was it observed in the buccinid L. dirum (Rivest 1983). It has, however, been reported in some other gastropods including Crucibulum quiriquinae (Véliz et al 2001), Crepidula coquimbensis (Véliz et al 2003;Brante et al 2009) Trophon geversianus (Cumplido et al 2011) and a vermetid gastropod (Strathmann and Strathmann 2006).…”
Section: Embryonic Development and Intracapsular Contents Datamentioning
confidence: 96%
“…However, there is also evidence of negative effects even at P O2 values similar to those we used (8 kPa), which may not be classified by ecologists as being environmental hypoxia (Vaquer-Sunyer and Duarte, 2008). While the survival of the encapsulated slipper limpet, C. coquimbensis, was not significantly affected by exposure to P O2 of ∼11.5 kPa (Brante et al, 2008), Brante et al (2009) later found that aerobic metabolism of embryos of this species and the related C. fornicata decreased significantly at P O2 <12 kPa. Similarly, development, hatching and shell secretion of the encapsulated muricid snail Chorus giganteus were all compromised by culture in seawater of P O2 ∼10 kPa (Cancino et al, 2003(Cancino et al, , 2011 and embryonic development of N. festivus was significantly delayed when cultured at a P O2 of ∼7.6 kPa (Chan et al, 2008).…”
Section: Hypoxia-induced Developmental Plasticitymentioning
confidence: 67%
“…The development rate of marine embryos and larvae has been linked to the maternal provisioning they receive. Brante et al (2009), for example, showed that supplying additional albumen to embryos of the slipper limpet, C. fornicata, enhanced growth rate. Although we did not measure albumen levels in the eggs of L. obtusata throughout their development, we did quantify albumen levels (measured as the diameter of albumen within the egg capsule) from images at the start of development.…”
Section: Which Embryos Survived Hypoxia?mentioning
confidence: 99%